2019
DOI: 10.1101/853366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct neural contributions to metacognition for detecting (but not discriminating) visual stimuli

Abstract: Being confident in whether a stimulus is present or absent (a detection judgment) is qualitatively distinct from being confident in the identity of that stimulus (a discrimination judgment). In particular, in detection, evidence can only be available for the presence, not the absence, of a target object. This asymmetry suggests that higher-order cognitive and neural processes may be required for confidence in detection, and more specifically, in judgments about absence. In a within-subject, pre-registe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 59 publications
9
51
3
Order By: Relevance
“…Building on our factorial design, we included linear and quadratic terms for coherence and context as parametric modulators of the neural response to the context screen. In this model, the quadratic context term captures the intuition that larger shifts in the mapping from private to public confidence are required when playing with both low-confidence and high-confidence partners ( Figure 3B ), whereas the quadratic coherence term controls for potential non-linear influences of an internal sense of confidence on the neural response ( Mazor et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Building on our factorial design, we included linear and quadratic terms for coherence and context as parametric modulators of the neural response to the context screen. In this model, the quadratic context term captures the intuition that larger shifts in the mapping from private to public confidence are required when playing with both low-confidence and high-confidence partners ( Figure 3B ), whereas the quadratic coherence term controls for potential non-linear influences of an internal sense of confidence on the neural response ( Mazor et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, it is increasingly recognised that the type of the task for the type I question plays an important role in metacognitive performance. Lee et al (2019) and Mazor et al (2020) showed dissociations both behaviourally and in the neural mechanisms involved in the computation of confidence following discrimination vs. detection tasks. This might be the reason why the literature on domain specificity yields a somewhat mixed picture (Rouault et al, 2018).…”
Section: Dissociations Between Tasks In Metacognitive Monitoringmentioning
confidence: 99%
“…Lee et al (2018) showed that the way the type I task is formulatedwhether it is a detection or discrimination taskaffects measures of metacognition, and suggested that discrimination tasks should be used in order to avoid response biases typical in detection tasks. Moreover, recent evidence suggests that confidence judgments following discrimination and detection decisions rely on partially different neural signatures (Mazor et al, 2020).…”
Section: Motor Metacognition: the Current State Of Researchmentioning
confidence: 99%
“…where observers can in principle process both positive and negative evidence for a particular outcome, and more like detection tasks (e.g., was there a line or not?). Intriguingly, observers in perceptual tasks tend to have poorer insight into their ability to judge absence over presence ( Kanai et al, 2010 ; Meuwese et al, 2014 ), possibly because the former places particular demands on metacognitive self-monitoring mechanisms ( Mazor et al, 2020 ). This asymmetry may have important implications for how agents actively monitor what they cannot control in certain kinds of environments ( Wen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%